Lixiviação e persistência de ametryn em solos da região canavieira do nordeste brasileiro - Silva, Kaliane de Souza (2016)
The use of herbicides without the basic knowledge of their interactions with soil and climate is a high risk of environmental contamination and loss of biodiversity. To avoid these problems is essential to understand the dynamics of the herbicide in the soil. Two experiments were conducted to evaluate the dynamics of ametryn in five soils of sugar cane region of Northeast Brazil: Quartzipsamment; Ultisol; Spodosol; Oxisol and Cambisol. The first experiment evaluated the leaching ametryn in said soil by means of liquid chromatography and bioassay. It was observed that the leaching of the herbicide was influenced by the physicochemical characteristics of the soil, with the following leaching potential sequence: Quartzipsamment> Oxisol> Ultisol> Cambisol> Spodosol and the Quartzipsamment showed higher concentration of ametryn the layer 5 to 10 cm deep, indicating possible loss of agronomic efficiency and contamination of groundwater. The second experiment evaluated the persistence of ametryn in soils mentioned by bioassays and liquid chromatography. It was noted that the persistence of the herbicide varied depending on the physical and chemical properties of the soil, with a halflife (t ½) of 49 days to Quartzipsamment, 35 days for Ultisol, 28 days for Spodosol, Oxisol and Cambisol. Intoxication visual symptoms caused by ametryn occurred up to 133 days to Quartzipsamment and Spodosol, 168 days for Ultisol, Oxisol and Cambisol